Molecular Detection of Babesia bovis Isolated from Cows in Thi-Qar Province - Mater, Abbas (University of Thi-Qar Journal of Science, 2025)
The present study was designed to determine the bovar2A gene in Babesia bovis Thus gene encodes a variant erythrocyte surface antigen that is unique to B. bovis was detected in the blood of infected cows in Thi-Qar province during the period of February to June 2019. A total of 96 blood samples were collected from the cows of both sexes. The Polymerase Chain Reaction (PCR)is  used to detect the bovar2A gene in Babesial infection status in cows. The PCR was used to distinguish Babesia bovis with a high level of sensitivity, capable to detection every species of B. bovis, and no evidence of non-specific amplification. The PCR results showed the bovar2A gene was harbored in 64 of 96 samples (66.66%) of Babesia bovis. The current study concluded that the bovar2A gene is useful for diagnosing B. bovis and the rising incidence of the disease in southern Iraq.